The Meaning of Monument in the Life of Toba Batak Tribe in Palipi Subdistrict, Samosir Regency, Indonesia - Ulung Napitu; Corry; Resna Napitu; Supsiloani (Budapest International Research and Critics University, 2020)
This study aims to analyze the meaning of monument in the life of Toba Batak tribe in Palipi Subdistrict, Samosir Regency. This research uses descriptive analytic method with phenomenology approach. Researchers in the phenomenological view try to understand the meaning of events and their relation to ordinary people in certain situations. The results of this study indicate that the monument is one place that will unite a clan and clan groups. The monument in Toba Batak community in Samosir is called the Procurement Monument where with the monument, a clan group will more often make offerings to its ancestors. In addition, with the existence of the monument, it is expected that fellow clans will meet and silaturrahmi relations will be maintained between clan relatives. In this study there were six monuments discussed as samples, namely Sitohang clan, Sinaga clan, Situmorang clan, Toga Pandiangan Tugu clan which was found in Palipi Subdistrict.